2015
DOI: 10.1364/oe.23.033018
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of soft X-ray reflectivity and interface stability in nitridated Pd/Y multilayer mirrors

Abstract: Pd/Y multilayer mirrors operating in the soft X-ray region are characterized by a high theoretical reflectance, reaching 65% at normal incidence in the 8-12 nm wavelength range. However, a severe intermixing of neighboring Pd and Y layers results in an almost total disappearance of the interfaces inside the multilayer structures fabricated by direct current magnetron sputtering and thus a dramatic reflectivity decrease. Based on grazing incidence X-ray reflectometry and X-ray photoelectron spectroscopy, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…(7). In contrast to the established equivalence of adjointness of the matrix form H of the Maxwell's equations in Xu's work 42 and Lorentz reciprocity, where H is 3D operator, the operatorL is a 2D differential operator. Interestingly, the self-adjointness of the operatorL is also a necessary and sufficient condition to material reciprocity.…”
Section: A Waveguide Reciprocity and Orthogonal Relationmentioning
confidence: 95%
See 3 more Smart Citations
“…(7). In contrast to the established equivalence of adjointness of the matrix form H of the Maxwell's equations in Xu's work 42 and Lorentz reciprocity, where H is 3D operator, the operatorL is a 2D differential operator. Interestingly, the self-adjointness of the operatorL is also a necessary and sufficient condition to material reciprocity.…”
Section: A Waveguide Reciprocity and Orthogonal Relationmentioning
confidence: 95%
“…We will refer Eq. (21) as GCMF, in order to be distinct from previous coupled mode equations, typically from Haus and ours 32,42 .…”
Section: Generalized Coupled Mode Formalism By Perturbationmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential applications vary from EUV spectroscopy, plasma diagnosis to synchrotron radiation or free electron laser instruments. A crucial factor is found that may compromise the performance of the mirror: the interdiffusion of Pd and Y. Nitridation of the Pd/Y multilayer by introducing nitrogen during the deposition process can reduce the interdiffusion [2,3]. Yet the nitridated multilayers suffer a reflectance loss.…”
mentioning
confidence: 99%